2012
DOI: 10.1108/00021461211277268
|View full text |Cite
|
Sign up to set email alerts
|

Is agricultural microcredit really more risky? Evidence from Tanzania

Abstract: PurposeUsing a unique dataset of a commercial microfinance institution (MFI) in Tanzania, the purpose of this paper is to investigate first whether agricultural firms have a different probability to get a loan and whether their loans are differently volume rationed than loans to non‐agricultural firms. Second, the paper analyzes whether agricultural firms repay their loans with different delinquencies than non‐agricultural firms.Design/methodology/approachThe authors estimate a Probit‐Model for the probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 36 publications
11
65
1
2
Order By: Relevance
“…Consistent with the logit model, coefficients on land holding and crop revenues are negative and significant. We do not find a gender effect, a result consistent with results from the multinomial logit and binary logit models, as well as findings by Weber and Musshoff (2012) on access to credit in Tanzania.…”
Section: Estimation Issues and Regression Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the logit model, coefficients on land holding and crop revenues are negative and significant. We do not find a gender effect, a result consistent with results from the multinomial logit and binary logit models, as well as findings by Weber and Musshoff (2012) on access to credit in Tanzania.…”
Section: Estimation Issues and Regression Resultssupporting
confidence: 90%
“…Stiglitz and Weiss (1981) define credit rationing as a situation in which either some loan applicants who are indistinguishable from others are denied loans even if they are willing to pay a higher interest rate, or some distinct groups of individuals are unable to acquire credit at any interest rate, but could do so at a higher level of credit supply. Credit rationing has been observed in Tanzania (Bigsten and Danielson 2001;Weber and Musshoff 2012) and certainly credit application is not costless for remote rural households. The methodological implication of omitting from the analysis households that did not seek for credit is that it could lead to biased results.…”
Section: Empirical Approachmentioning
confidence: 99%
“…The research was based on the example of a Tanzanian MFI. Weber and Musshoff (2012) showed that agricultural clients do face obstacles in accessing loans, which confirms the initial perception that these clients are riskier. However, Weber and Musshoff (2012) found agricultural loans actually show a better repayment performance than non-agricultural loans.…”
Section: Literature Review and Hypothesessupporting
confidence: 60%
“…In this context, Weber and Musshoff (2012) investigated whether agricultural lending is indeed more risky than non-agricultural lending. The research was based on the example of a Tanzanian MFI.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In consequence, profitable projects cannot be realized at all or only with higher repayment risks when cash flow and repayment obligations do not match (Field et al, 2011). Hence, product standardization might reduce default risks for clients with continuous cash flows but limits the focus of MFIs to projects fulfilling the product requirements (Weber and Musshoff, 2012). Unsurprisingly, most MFI clients are traders with fast turnovers, using their loans to finance mainly working capital.…”
Section: Lending Principles In Microfinancementioning
confidence: 99%